Aspects of cost reduction for highway bridges in Myanmar - Singh, Dharmendar. (2008)
The goal of this thesis work is to develop general guidelines for cost reduction methodology that would make efficient use of construction materials and technology in obtaining the optimal bridge design taking into account all expected cost from the design stage to the end of bridge life span. This cost includes agency costs, user costs and external costs.